From Yemen war to joint army? Egyptian-Saudi differences over Arab military cooperation - Jessica Noll; Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2015)
On 25 March 2015 a Saudi-led coalition of Arab states launched air strikes on Yemen to halt the advance of the Houthi movement. A few days later the summit of the Arab League decided to set up a joint Arab army. Nevertheless, the two most important Arab countries support opposing concepts for military cooperation: Egypt proposes institutionalised long-term military cooperation to increase its political weight in the region, while Saudi Arabia prefers ad hoc coalitions precisely in order to avoid long-term dependency on other countries, not least Egypt. However, the two events suggest that states in the region are stepping up military cooperation. Germany and the European Union should treat this development with scepticism. Experience shows that such collaborations tend to exacerbate rather than resolve regional conflicts. (SWP Comments)
Keywords: 320